Taking Matters into our Own Hands: Humanizing Slovak Translation History - Tyšš, Igor; Gromová, Edita (Porównania, 2020)
Translation history has always played an important role in Slovak literary and translation studies. In our paper we discuss the beginnings of Slovak translation history research, which have their roots in formalism and structuralism, and reconstruct lines of influence to the present when translation history is a lively, open, interdisciplinary, and empirical discipline. With the past in mind, we look at several of the most recent and significant research initiatives in Slovak translation history research and evaluate their potential for the future.